The Role Of Brand Image In Mediating Service Quality And Promotion Towards Decisions To Buy Car On Credit In The Covid-19 Period (Study Case At Pt Maybank Indonesia Finance Dki Jakarta And Tangerang Branch) - Saparso; Soegeng Wahyoedi; Santoso (International Journal of Science, Technology & Management, 2021)
This study discusses the role of brand image in mediating service quality and promotion of car purchase decisions on credit during the Covid-19 period at PT Maybank Indonesia Finance. This research was conducted by using the probability sampling method with the type of simple random sampling. Researchers distributed questionnaires to 100 Maybank Finance consumer respondents in DKI Jakarta and Tangerang. Data analysis using Smart PLS analysis. The results of the analysis conclude that service quality has a positive and significant influence on purchasing decisions. It can be said, good service quality will affect the decision to buy a car on credit at Maybank Finance. The promotion has a positive and significant influence on purchasing decisions. It can be said that the company's promotions will influence the decision to purchase a car on credit at Maybank Finance. Service quality has a positive and significant influence on brand image. Good service quality will form a good brand image in the minds of consumers. The promotion has a positive and significant influence on brand image. If the promotion is increasing, it will affect the company's brand image. Brand image has a positive and significant influence on purchasing decisions. A good brand image will influence the decision to buy a car on credit at Maybank Finance. Brand image is also proven to have a role in mediating service quality on purchasing decisions.